O-226 The microscopic se men improvement after surgical varicocele repair. (6th August 2021) - Melli, B; Morini, D; Daolio, J; Nicoli, A; De Feo, G; Valli, B; Viola, D; Colla, R; Spaggiari, G; Santi, D; Simoni, M; Aguzzoli, L; et al.
Abstract: Study question: Evaluation of the effect of varicocele correction on conventional and microscopic seminal parameters and evaluation of which factors might predict sperm improvement after surgical treatment. Summary answer: The detailed morphologic sperm evaluation has been identified as a novel parameter expressing the post-surgical semen amelioration after varicocelectomy. What is known already: Generally, varicocele develops during puberty and occurs more often on the left side for anatomic reasons. However, its diagnosis is commonly delayed, especially in asymptomatic cases, until the man consults an andrologist for couple infertility. A causative relationship between varicocele and impairment of semen quality has been largely investigated in the context of male infertility. Despite the florid literature available on this topic, the clinical benefit in terms of semen quality improvement after varicocele surgical repair remains controversial. Study design, size, duration: An observational, retrospective clinical trial was carried out including patients undergoing surgical treatment for varicocele at the Day Surgery of the Urology Operative Unit of the Santa Maria Nuova Hospital-IRCCS of Reggio Emilia from September 2011 to March 2020. Primary outcome was the detailed morphologic microscopic sperm evaluation. Secondary outcomes were conventional semen analyses. Each patient was considered two times (before and after the surgery) and evaluated by both physical examination and ultrasonography. Participants/materials, setting, methods: The inclusion criteria considered the patients with diagnosis of varicocele at ultrasound examination, attending surgical resolution and with at semen analyses before and after the surgery, were excluded patients with diagnosis of varicocele without surgical indication, and/or semen analyses performed only before or only after the surgery. In the statistical analysis a logistic multivariate regression analysis was performed in order to evaluate the change before and after surgery. Main results and the role of chance: The post-surgical semen analysis was performed after a mean of 183.7 + 112.5 days since the surgery for a total of 121 males (mean age 24.6 + 4.1 years) enrolled. The surgical treatment leads to a significant increase in sperm concentration (p = 0.015) and percentage of progressive and total motility (p = 0.022 and p = 0.039, respectively), with a significant decrease in the percentage of immobile sperms (p = 0.013). In particular, semen concentration improved in 71.7% of patients (p = 0.010). Considering the detailed morphologic microscopic evaluation, a significant improvement was detected: head abnormalities showed a significant reduction, considering microcephaly (3.3 + 3.6 versus 2.2 + 2.9%, p = 0.015), macrocephaly (1.4 + 0.6 versus 1.2 + 0.9%, p = 0.043) and cytoplasmic appendix (1.4 + 0.8 versus 0.9 + 1.2%, p = 0.041). Moreover, surgery led to a significant reduction of tails abnormalities, considering absence (0.6 +2.3 versus 0.1 + 0.7, p = 0.048) and coiled tail (5.2 + 1.5 versus 6.6 + 2.0, p = 0.037). Thus, surgical varicocele resolution leads to a significant improvement in specific morphological semen parameters. The multivariate logistic analysis identified the ultrasound varicocele degree before surgery as a main predictor of the sperm concentration improvement (p = 0.016). The semen parameters improvement was higher for varicocele of I and II degree (p = 0.008). Limitations, reasons for caution: The retrospective study design precluded from carrying out a case-control study to compare the surgical techniques. Moreover, the study design limited the availability of patients' clinical data in order to performed a more comprehensive predictive analysis. Wider implications of the findings: Using a complex statistical approach, it emerged that the greatest improvement in semen quality was obtained in case of mild varicocele, increasing the knowledge on the therapeutic potential of surgery. This result has clinical implications, since it could help to select those patients 'to treat or not to treat'. Trial registration number: none